Analisis Sistem Antrian Pada Pelayanan Poli Jantung RSUD Kota Langsa - Fazrina Saumi; Rizki Amalia; Amelia; Nurviana (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2021)
Queuing is an activity where parties are waiting to get service. A queuing process starts from the time of arrival to the time of service. Queuing problems are often encountered in everyday life, including in Langsa City Hospital, especially in the cardiac clinic, which has the most patients. The majority of patients in the queue system are elderly (elderly), so good service is needed considering the physical condition of patients who have entered a vulnerable age. The queuing system analysis aims to determine the average number of patients waiting in the system and the length of service at the heart clinic of Langsa City Hospital. In addition, the queue system analysis can help the Langsa City Hospital design an operational service system so that the service process can run optimally. The queue structure model used is a single channel-single phase with the discipline type First In First Out (FIFO). From the queue model analysis results obtained, the cardiac poly care system has an average number of patients waiting at most occurs in the period 08.00-10.00, namely 14 people with a waiting time of about 56.28 minutes. This time is the busy working hour at cardiac poly with a busyness rate of 93%. From the simulation results with two servers using the same model, a busy rate of 50% was obtained with a reduction in the number of people waiting by 12.8 people with a waiting time of about 1.2 minutes.